2020
DOI: 10.47176/mjiri.34.84
|View full text |Cite
|
Sign up to set email alerts
|

Gender role conflict: Is it a predictor of marital dissatisfaction? A cross sectional study in Tehran

Abstract: Gender role conflict was related to low marital satisfaction and those who had feminine and androgynous gender roles reported more marital satisfaction. Some of the feminine characteristics, which are a combination of complex behavioral and emotional interactions, can enhance the relationships. These results can be used in marital counseling and therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Recent studies indicate that the spouses of men with gender role conflict experience less marital satisfaction and more depression and anxiety. Gender role conflict in men is, therefore, riddled with intra-and interpersonal consequences that disrupt the family's function [18]. It can thus be concluded that men's gender role conflict is significantly related to their novelty-seeking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies indicate that the spouses of men with gender role conflict experience less marital satisfaction and more depression and anxiety. Gender role conflict in men is, therefore, riddled with intra-and interpersonal consequences that disrupt the family's function [18]. It can thus be concluded that men's gender role conflict is significantly related to their novelty-seeking.…”
Section: Discussionmentioning
confidence: 99%
“…Men try to perform the expected gender roles while disregarding their possible negative impacts. Based on the gender role conflict model, roles that restrict the process of socialization are acquired in patriarchal and traditional societies and harm both women and men [18]. Recent studies indicate that the spouses of men who have gender role conflict experience less marital satisfaction and more depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Individuals and families can attain better financial goals and enhance financial wellbeing if budgetary control is rationally achieved. Therefore, effective financial planning enhances marital SF by mitigating the burden of economic stress and its harsh consequences on families (Pourshahbaz et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals and families can attain better financial goals and enhance financial wellbeing if budgetary control is rationally achieved. Therefore, effective financial planning enhances marital SF by mitigating the burden of economic stress and its harsh consequences on families (Pourshahbaz et al, 2020). Given that Qatar is the wealthiest country in the world per capita, social instability, marital disharmony and poor morality are more causative than financial dilemmas in leading couples to seek divorce.…”
Section: Likelihood Of Seeking a Divorcementioning
confidence: 99%
“…Furthermore, the existing literature provides support for an indirect association between subjective deviance from traditional male gender roles and negative consequences in men's close relationships. More specifically, GRC has been found to predict psychological well-being, relationship satisfaction (Pourshahbaz, 2020;Rochlen & Mahalik, 2004), and overall interpersonal functioning (Breiding et al, 2008). It also correlates with self-esteem (Mahalik et al, 2001), personality (Schwartz et al, 2004), coping and problem-solving strategies (Szymanski & Carr, 2008), body image, and muscularity (Gattario et al, 2015;Hobza & Rochlen, 2009;Manley et al, 2007;McCreary et al, 2005;Mejias, 2010;Murray & Lewis, 2014;Schwartz et al, 2010;Shepherd & Rickard, 2012;Schwartz & Tylka, 2008).…”
Section: Introductionmentioning
confidence: 99%